1999
DOI: 10.1111/j.1752-1688.1999.tb04234.x
|View full text |Cite
|
Sign up to set email alerts
|

CLIMATE VARIABILITY AND FLOOD FREQUENCY ESTIMATION FOR THE UPPER MISSISSIPPI AND LOWER MISSOURI RIVERS1

Abstract: This paper considers the distribution of flood flows in the Upper Mississippi, Lower Missouri, and Illinois Rivers and their relationship to climatic indices. Global climate patterns including El Niño/Southern Oscillation, the Pacific Decadal Oscillation, and the North Atlantic Oscillation explained very little of the variations in flow peaks. However, large and statistically significant upward trends were found in many gauge records along the Upper Mississippi and Missouri Rivers: at Hermann on the Missouri R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
100
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 10 publications
5
100
0
3
Order By: Relevance
“…The most obvious question is: when did the effect of climate change begin to significantly influence the hydrologic variable of interest, e.g., annual maximum peaks? For example, Olsen et al (1999) varied the start and end dates of flood records analyzed for gauges in the Missouri and Mississippi River basin. Based on the linear regression results, they found that different record lengths within the same flood record influenced the significance of the trend detected.…”
Section: The Assumption Of a Start Timementioning
confidence: 99%
“…The most obvious question is: when did the effect of climate change begin to significantly influence the hydrologic variable of interest, e.g., annual maximum peaks? For example, Olsen et al (1999) varied the start and end dates of flood records analyzed for gauges in the Missouri and Mississippi River basin. Based on the linear regression results, they found that different record lengths within the same flood record influenced the significance of the trend detected.…”
Section: The Assumption Of a Start Timementioning
confidence: 99%
“…따라서 많은 학자들은 이와 같은 현상을 배경으로 하여 자료의 특성이 시간의 흐름에 따라 변화가 없는 것으로 보는 정상성 가정이 아닌 시간의 흐 름에 따라 변화한다고 보는 비정상성(nonstationarity) 가 정에 대한 연구가 활발히 진행 중에 있다. 이러한 비정상 성을 고려한 빈도해석에 대한 연구는 1990년대 말부터 논 의가 서서히 진행되었으며 주로 특정 분포형의 매개변수 에 경향성을 반영한 빈도해석이 주를 이루고 있다 (Olsen et al, 1999;Coles, 2001;Katz et al, 2002;Cunderlik and Burn, 2003;Nadarajah, 2005;He et al, 2006;El Adlouni et al, 2007). 국내의 경우에도 연최대강우량과 해수면온 도와 같은 수문 및 기상 인자들의 추세와 통계적 특성 등 을 분석하고 자료의 경향성이 나타나는 지점의 분포모형 과 분석된 자료와의 상관관계를 바탕으로 비정상성 빈도 해석을 수행하는 연구가 진행 중이다 (Kwon et al, 2009;Kwon and Lee, 2011;Jang et al, 2011;Kim et al, 2011;Seo et al, 2012).…”
unclassified
“…Nonstationarity in hydroclimate extremes has emerged as a prevailing issue in water resources engineering and hydrology over the past two decades [Olsen et al, 1999;Koutsoyiannis, 2006;Khaliq et al, 2006;Villarini et al, 2009]. Large-scale oscillations in the climate system (e.g., El-Niño Southern Oscillation, Pacific Decadal Oscillation) have been shown to modulate the frequency distributions of extreme hydroclimate events around the world, challenging the statistical assumptions underlying classical extreme value frequency analysis [Jain and Lall, 2000;Kwon et al, 2008;Alexander et al, 2009;Lima and Lall, 2010;Ward et al, 2010].…”
Section: Introductionmentioning
confidence: 99%